Peran Digital On-Line [DO] dalam Pengadaan Yang Berkeadilan Sosial bagi Seluruh Rakyat Indonesia - Mulawardana, Junaedi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Procurement in government synergy is one of the activities that plays an important role in the running of a Ministry, Institution and Regional Government. When a procurement process is hampered, it is certain that activities on Ministry, Institution and Regional Government will be affected, both in terms of budget absorption and the output. In the procurement activities there are many factors that cause the procurement process to not run as it should, it can be caused by technical and nontechnical constraints. Evaluation of rules and methods of change is one solution to minimize it. On-line procurement methods are the right solution to conduct procurement that is efficient, effective, transparent, open, competitive, fair and accountable. Because this will cut the direct relationship between the buyer with the provider, So the results of this procurement process will be utilized by the Indonesian people both directly and indirectly as users of the results of all procurement processes carried out by Ministry, Institution and Regional Government.